Role of Products Element In Determining Decisions of Purchase - Dedi Iskamto (Inovbiz: Jurnal Inovasi Bisnis, 2020)
This study aims to find a correlation between the effects of the product both in terms of Variations in size or shape of the product, product quality, type of product, product utilization and product durability to the consumer's decision to buy the product. This research is a quantitative study in which to process research data using SPSS 21. This research was conducted in Kuansing Regency, Riau Province. The number of samples in this study were 210 with simple random sampling technique. The results of data processing obtained that the hypothesis testing with the t test there is an existence of t-count of 25.904 means t-count = 25.904> t-table = 1.996 which means the product has a significant effect on consumer buying decisions. The value of the determinant coefficient (R2) is 0.910